Vertical component effects of earthquake and soil-structure interaction on steel gabled frames. (September 2022) - Malekizadeh, Mohammad; Fanaie, Nader; Pirasteh, Ali Akbar
Abstract: With an increase in the width of the steel gabled frame (SGF) span, in general, the structural mass considerably increases, as a result of which the vertical ground motions can exert significant inertial force on the members of a structure. Although numerous studies have confirmed the destructive effects of the vertical component of earthquake on concrete and steel structures, no research has been devoted to the impact of this component on steel gabled structures yet. Hence, the findings of this research will, at best, unveil possible new dimensions of these types of structures. Moreover, the investigation into the behavior of such structures with regard to the effects of soil-structure interaction (SSI) can help gain a more accurate understanding of their behavior. To this aim, in the present paper, an incremental dynamic analysis (IDA) was conducted for the first time on four SGFs with spans of 20 m and 60 m and heights of 6 m and 12 m with and without consideration of the vertical component of earthquake as well as SSI. Results were collected in the form of multi-record IDA curves, summarized IDA curves, fragility curves and probabilistic seismic demand analysis (PSDA) curves, indicating that the vertical component of earthquake had a determinative role on the seismic performance of wide-span SGFs. This component causes the structure to reach the nonlinear region more quickly, raises the stiffness changes in the nonlinear region, enlarges the data dispersion and demand sensitivity, intensifies the softening behavior, reduces the dynamic capacity, raises the failure probability, enhances the uncertainty, increases the mean annual frequency (MAF) and accelerates the damage in such structures. However, SSI does not have any significant role in the seismic performance of SGFs; just partially leading to more conservative results, especially when they have wide spans. Besides, the results of the PSDA analysis showed that under similar conditions, short-period SGFs are more vulnerable than long-period SGFs and should be prioritized for retrofitting. Graphical abstract: Unlabelled Image Highlights: The vertical component of earthquake is very important for the wide-span SGFs. The vertical component of earthquake is not much important for the short-span SGFs at the IO performance level. SSI is not much important for the SGFs; just partially leading to more conservative results, especially when they have wide spans. The effect of the vertical component of earthquake in nonlinear regions is much greater than in linear regions. SSI has almost the same effect in both the linear and nonlinear regions.